2011
DOI: 10.1073/pnas.1107692108
|View full text |Cite
|
Sign up to set email alerts
|

Calpain interacts with class IA phosphoinositide 3-kinases regulating their stability and signaling activity

Abstract: Class IA phosphoinositide 3-kinases (PI3Ks) are signaling enzymes with key roles in the regulation of essential cellular functions and disease, including cancer. Accordingly, their activity is tightly controlled in cells to maintain homeostasis. The formation of multiprotein complexes is a ubiquitous mechanism to regulate enzyme activity but the contribution of protein-protein interactions to the regulation of PI3K signaling is not fully understood. We designed an affinity purification quantitative mass spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 49 publications
0
23
0
1
Order By: Relevance
“…Recently, it has been suggested that calpain is capable of partially modulating cellular proliferative signals dependent on the PI3K/mTOR signaling pathway [22]. In cases of cardiac disease, where there is no effective process of neo-vascularization, repair and tissue regeneration may be limited or may not occur.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been suggested that calpain is capable of partially modulating cellular proliferative signals dependent on the PI3K/mTOR signaling pathway [22]. In cases of cardiac disease, where there is no effective process of neo-vascularization, repair and tissue regeneration may be limited or may not occur.…”
Section: Discussionmentioning
confidence: 99%
“…Recent, evidence indicates that calpain plays a dual role in protein metabolism through the concomitant activation of proteasome-dependent proteolysis and inhibition of the PI3K/Akt protein synthesis pathway [22]. Furthermore, mTOR inhibition mediated by calpain could potentially reduce the overall rates of protein synthesis, reducing the available translational machinery required for the maintenance of the protein synthesis levels [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the regulation of proteolytic activity is complex and involves the association of calpain with a regulatory subunit, the endogenous inhibitor calpastatin, 4 other interacting proteins, 5 and binding to phospholipids. 6,7 Genetic deletion of m-calpain results in embryonic lethality, 8,9 but -calpain Ϫ/Ϫ mice are viable and demonstrate attenuated aggregation and clot retraction but normal bleeding times. 10 Mechanistically, the latter effects were attributed to the tyrosine dephosphorylation of platelet proteins because -calpain Ϫ/Ϫ platelets exhibited high levels of tyrosine phosphatase 1B protein and activity.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies have shown that calpain may inhibit insulin signaling [50][53]. We also examined how calpain inhibition would affect the inhibitory effect of DEX on D6, when no activation of μ-calpain was observed upon DEX treatment (D6, lane 2, Fig.…”
Section: Resultsmentioning
confidence: 99%